2014
DOI: 10.1007/s10459-014-9564-y
|View full text |Cite
|
Sign up to set email alerts
|

What students really learn: contrasting medical and nursing students’ experiences of the clinical learning environment

Abstract: This paper explores and contrasts undergraduate medical and nursing students' experiences of the clinical learning environment. Using a sociocultural perspective of learning and an interpretative approach, 15 in-depth interviews with medical and nursing students were analysed with content analysis. Students' experiences are described using a framework of 'before', 'during' and 'after' clinical placements. Three major themes emerged from the analysis, contrasting the medical and nursing students' experiences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 26 publications
1
39
0
3
Order By: Relevance
“…A welcome introduction to the department, a sense of belonging and teamwork, and student‐centred supervision have been identified as prerequisites for effective learning and patient care . Our data add to this by highlighting a number of points that may be valuable for practitioners to consider when looking to better understand and perhaps direct improvements in their own CLE.…”
Section: Discussionmentioning
confidence: 60%
“…A welcome introduction to the department, a sense of belonging and teamwork, and student‐centred supervision have been identified as prerequisites for effective learning and patient care . Our data add to this by highlighting a number of points that may be valuable for practitioners to consider when looking to better understand and perhaps direct improvements in their own CLE.…”
Section: Discussionmentioning
confidence: 60%
“…Study I [10] demonstrated how medical students accepted the placement as it was and they reported on not taking any actions if, for example, a placement did not work according to their expectations. Medical students experienced that they needed to promote themselves for supervisors to engage with them and they emphasized how they learned by observing supervisors’ practice.…”
Section: Resultsmentioning
confidence: 99%
“…There might also be cultural differences between the 2 professions regarding teaching and learning, a point highlighted between medical and nursing students. 36 However, contrasting teachers' experiences of these 2 environments can be a first endeavor toward highlighting such cultural discrepancies.…”
Section: Discussionmentioning
confidence: 99%